An innovative package of training techniques effectiveness in Taekwondo - Mischenko, N.; Kolokoltsev, M.; Vorozheikin, A.; Romanova, E.; Bolotin, A.; Aganov, S.; Velikaya, O. (Journal of Physical Education and Sport, 2021)
Nowadays, there is not enough scientific and methodological literature, reflecting materials on innovative techniques «CrossFit», «Rope-skipping», «Tai-bo» and «Ki-bo» use in female taekwondo athletes' training process. The research purpose is: to experimentally prove the effectiveness of using an innovative training techniques package to increase the general, special endurance, technical and tactical level of WTF taekwondo athletes (female). Material and methods of research. The pedagogical experimental project involved 2 groups of girls aged 16-17 (n=20) who were engaged in WTF taekwondo at a sports school in Chelyabinsk (Russia) according to a generally accepted program. An innovative package of techniques was added to the program of the annual cycle of the training process in the experimental group (EG, n=10), which contained a set of elements «CrossFit», «Rope-skipping», «Tai-bo» and «Ki-bo» aimed at improving the athletes' general and special endurance and technical and tactical skills. In the experimental program, the innovative training package methods of the annual macro-cycle were replaced every two months. A «Fightball» simulator was used to develop and practice striking techniques with hands and elbows. For a comparative analysis of the training process programs effectiveness in both groups, the met hods of high-stakes testing of general, special endurance and technical and tactical skills were used. Results. At the end of the pedagogical experiment, the girls of both observation groups had an improvement in the values of all tests indicators. A significant increase in the indicators values was registered only in EG girls in all physical fitness tests (with the exception of «shuttle run 3 x 8 m»). The greatest increase was found in EG girls in tests for flexibility (36.5%) and speed endurance (33.7%). In tests for speed and strength endurance, the indicators values were higher in EG by 22.2% and 20%, respectively, than in girls of CG. The girls' in both groups indicators values of technical readiness increased. The greatest increase (50%) in the technical readiness indicators values was noted in EG girls in tests characterizing the striking abilities of the arms and legs. The increase in the tactical actions indicators of the EG girls turned out to be higher, compared with the values of the indicators in the ?G. Conclusions. The research results proved the effectiveness of the proposed program of the annual training process to increase the level of WTF taekwondo athletes' general, special physical, technical and tactical readiness, which allows recommending it for wide use in athletes' training.